Penerapan Konsep Hotel Green Building di Kota dan Daerah Wisata, Aman Pada Masa Pandemi - Ricardianto, Prasadja; Ningrum, Lestari; Hendradewi, Savitri; Dewi, Triana Rosalina (Jurnal Ilmiah Pariwisata, 2022)
This study aims to provide an overview of the application of the concept of green or green concept in hotels. The desire to get a comfortable atmosphere is certainly supported by fresh air from nature in addition to other facilities such as cleanliness. In certain circumstances, hotel stays can be done in cities with high pollution levels. Green building concept hotel selection is certainly one of the considerations by some guests who indeed prioritize the comfortable atmosphere obtained from the fresh air. the same thing is more easily obtained at hotels located in mountainous areas or beaches, especially during a pandemic because of the covid 19. The research used descriptive research methods and survey methods were used through in-depth interviews. From the analysis of several hotels that claim to use the concept of green concept, the results obtained are not all hotels apply the concept of green concept entirely,even though the hotel is located in mountainous and coastal areas, whereas the green concept is very appropriate in using wisely and ensuring the continuity of the supply of natural resources and the environment in the future and maintaining air quality by optimizing air circulation and sunlight (CHSE standards). Keywords: Service Quality, Order Application, Come Directly